PERUBAHAN PENGGUNAAN LAHAN HUTAN SEKITAR SUNGAI KAMPAR, RIAU - Ishak Sumantri; Machfudh Wesman E; Haryono Haryono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
This study is to evaluate the trend of forest land-use change as a result of the community's activities in pursuing its need for settlement and land cultivation in forest land in the vicinity of Kampar river, Riau. To understand the trend of forest land utilization change, 4 data resource references including aerial photo 1964, general view of 1974 forest map, 1982 land use map, and a ground check in 1984, have been used. During two periods i.e., in the years from 1964 to 1974, and from 1974 to 1984, it is known that an invation occured into both limited production forest and conversion forest in the Sub Districts of Kampar Kiri and Sengingi. An analysis of data, using